Apakah Pandemi Covid-19 Mempengaruhi Risiko Sistemik Pada Dual Sistem Perbankan di Indonesia - Fitrotul Fardila; Yopi Yudha Utama (Al-Muraqabah: Journal of Management and Sharia Business, 2021)
The banking sector around the world is beneath enormous pressure because of the evolving COVID-19 scenario and its policy responses. This study investigates how this pandemic impacts the systemic risk of Islamic business banks (ICBs) and conventional commercial banks (CCBs) in Indonesia. This observation affords empirical proof concerning the estimation and resolution of systemic risk. In unique, using the spillover measure, we discover a substantial increase in systemic risk in a few of the sample banks. This look gives an in-depth contribution to the literature and suggests various coverage pointers, covered systematically figuring out critical establishments and supplied testimony approximately the blessings of coverage responses in addressing systemic risks.